Design and content perculiarities of the course ‘french for specific purposes’ in the technical university - Tatiana A. Fedorova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper discusses the didactic features of the French Language for Specific Purposes as goals and tools of learning, the design and content peculiarities of the course, and teacher’s principles on implementing the communicative and professional approach in the process of training. Carrying out the course ‘French for Specific Purposes’ based on students needs increases motivation and develops professional and personal orientation by means of language. Teaching the language for specific purposes helps to solve the problems of grammar integration and the selection of professionally significant situations, vocabulary and the components of the socio-cultural aspect of communication. The paper touches upon the practical aspect.